Shape‐Controlled Flexible Microelectronics Facilitated by Integrated Sensors and Conductive Polymer Actuators. (21st January 2021) - Rivkin, Boris; Becker, Christian; Akbar, Farzin; Ravishankar, Rachappa; Karnaushenko, Dmitriy D.; Naumann, Ronald; Mirhajivarzaneh, Alaleh; Medina-Sánchez, Mariana; Karnaushenko, Daniil; Schmidt, Oliver G.
Abstract : The next generation of biomedical tools requires reshapeable electronics to closely interface with biological tissues. This will offer unique mechanical properties and the ability to conform to irregular geometries while being robust and lightweight. Such devices can be achieved with soft materials and thin‐film structures that are able to reshape on demand. However, reshaping at the submillimeter scale remains a challenging task. Herein, shape‐controlled microscale devices are demonstrated that integrate electronic sensors and electroactive polymer actuators. The fast and biocompatible actuators are capable of actively reshaping the device into flat or curved geometries. The curvature and position of the devices are monitored with strain or magnetic sensors. The sensor signals are used in a closed feedback loop to control the actuators. The devices are wafer‐scale microfabricated resulting in multiple functional units capable of grasping, holding, and releasing biological tissues, as demonstrated with a neuronal bundle. Abstract : A reshapeable micro‐electronic device is demonstrated with either integrated strain or magnetic sensors, and feedback controlled conductive polymer actuators. Magnetic field sensors assess the device orientation while strain sensors measure the device curvature, which enables obstacle detection. These manipulators can grab, hold and release biological tissues, as demonstrated with a neuronal bundle, leading to intriguing applications as surgical micro‐clamps.